Performance and perception of dental students using a haptic simulator for tooth preparation of a metal-free crown - Pichilingue-Orbe, Angie Patricia (2026)
Objective: To describe performance and analyze the perception of dental students from a private university in Metropolitan Lima when using a haptic simulator for tooth preparation of a metal-free crown in the posterior region. Materials and methods: A cross-sectional, descriptive, and observational study was conducted. A total of 27 students participated, performing tooth preparation for a metal-free crown on a mandibular molar using the Simodont® Dental Trainer haptic simulator. Performance was assessed using a six-parameter rubric (maximum score: 20 points), and the activity was classified as pass (≥11) or fail (<11). Perception of the simulator’s usefulness was measured using a five-point Likert-type survey. Descriptive and bivariate analyses were conducted using nonparametric tests (p < 0.05). Results: 66.67% of students failed the global manual dexterity assessment. Occlusal reduction showed the highest proportion of unacceptable results (70.37%), and 100% of participants affected adjacent teeth. In contrast, the convergence angle showed 74.07% satisfactory results. Overall perception of the simulator was positive (median = 4). Significant associations were found between performance in occlusal reduction and perceived similarity to a real dental handpiece (p = 0.041) and handpiece control (p = 0.043), as well as between convergence angle and manual comfort (p = 0.010). Conclusions: Although students showed a favorable perception of the haptic simulator, technical performance was predominantly suboptimal. These findings suggest that positive perception does not necessarily translate into immediate clinical competence. Haptic simulation should be integrated in a structured and progressive manner within preclinical training, consistently incorporating instructor feedback.